The British Origins of the French Jacobins: Radical Sociability and the Development of Political Club Networks, 1787–1793. (October 2014) - Alpaugh, Micah
Approaching the Revolutionary era from a transnational perspective, this article explores the rich exchanges and collaborations between radical British and French popular societies. Both early French political and antislavery societies adapted their associational strategies from Anglo-American examples – indeed, borrowing the word 'club' itself to describe such organizations. Most significantly, in November 1789, correspondence from the London Revolution Society directly inspired the founding of the Paris Jacobin Club, and the integrated national network the Jacobins formed consciously built from British designs. By 1792, active experimentation proliferated in both nations as the Jacobins radicalized, and their example boomeranged to motivate the creation of a more integrated radical political network in Britain, the London Corresponding Society. Utilizing club correspondence, radical newspapers and pamphlets, and personal communications between key members, this article seeks to demonstrate the applied power of Revolutionary cosmopolitanism and transnational epistolary connections. Whereas prior scholarship of these connections has been largely limited to the French Revolution's influence on Britain, the extent of the British influence on the early Jacobins has been virtually ignored. This account attempts to highlight the rich mutual exchanges that inspired the most radical and influential movements of the Revolutionary age.